Kritik Kenabian Dalam Yeremia 23:9-40 dan Implikasinya Terhadap Fenomena Disinformasi di Era Digital - Perlindungan Lugu; Agus Kriswanto (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2025)
The rapid development of digital technology has accelerated and expanded the spread of misinformation and disinformation, affecting various aspects of life, including political, social, and religious spheres. This study analyzes the prophetic critique in Jeremiah 23:9–40 against false prophets and explores its implications for addressing contemporary challenges of disinformation. Employing a qualitative method with a literature-based approach, the research seeks to identify parallels between the misleading practices of false prophets in Jeremiah’s time and modern figures who disseminate false information for personal or group interests. The findings indicate that false prophets in the era of Jeremiah manipulated religious teachings for personal and political gain, a pattern comparable to contemporary influencers or public figures who spread disinformation for ideological purposes or financial benefit, either directly or through social media. These findings underscore the importance of theological literacy, critical awareness, and ethical leadership in resisting the erosion of truth within the open digital public sphere. This study further contributes to ongoing discussions on the role of biblical principles in guiding faith communities to engage with and respond to disinformation in the digital age in a wise and responsible manner.